2021
DOI: 10.4314/aas.v18i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Uptake of Prostate Cancer Screening in a Kenyan Rural Community

Abstract: Background: Prostate cancer (PC) is curable with early detection, yet it remains a major public health problem globally and a leading  cause of mortality among men. The objective of the study was to explore the barriers and facilitators to the uptake of prostate cancer screening among men aged 40–69 years in a rural community in Kenya. Methods: We utilized an explorative qualitative design and purposive sampling to select participants. Six focus group discussions (FGDs)  and seven in-depth interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Concerning to the reason for getting screened, the most common cause was the emergence of symptoms followed by worried about prostate cancer and all of them had negative results (Table 2). This result is congruent with Mbugua et al (2021) (19) who conducted a study to explore the barriers and facilitators to the uptake of prostate cancer screening among men aged 40-69 years in a rural community in Kenya and found that most of the participants reported that experience of symptoms, worried about prostate cancer were the main motivators for their prostate cancer screening. Commitment of men with prostate cancer screening is highly dependent on their knowledge about PC and the benefits of early detection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Concerning to the reason for getting screened, the most common cause was the emergence of symptoms followed by worried about prostate cancer and all of them had negative results (Table 2). This result is congruent with Mbugua et al (2021) (19) who conducted a study to explore the barriers and facilitators to the uptake of prostate cancer screening among men aged 40-69 years in a rural community in Kenya and found that most of the participants reported that experience of symptoms, worried about prostate cancer were the main motivators for their prostate cancer screening. Commitment of men with prostate cancer screening is highly dependent on their knowledge about PC and the benefits of early detection.…”
Section: Discussionsupporting
confidence: 85%
“…So, understanding of the disease and its screening continue to be important areas for discussion among the men population for early detection of the disease (18) . Studies have found that a lack of knowledge about the disease and its screening tests serves as a barrier to effective cancer prevention and control (19,20) . Dissemination of information via education programs about prostate cancer and its screening through different community settings can promote active engagement and commitment of men with screening (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of men with a history of PC screening was assessed. Knowledge was measured using 13 items [ 11 ] and perception of self-vulnerability was assessed using 11 items using a Likert scale ranging from strongly disagree (1) to strongly agree (5). The scores were computed for the level of agreement at baseline and postintervention.…”
Section: Methodsmentioning
confidence: 99%
“…Package of Social Sciences (SPSS) version 22. e proportion of men with a history of PC screening was assessed. Knowledge was measured using 13 items [11] and perception of self-vulnerability was assessed using 11 items using a Likert scale ranging from strongly disagree (1) to strongly agree (5).…”
Section: Data Analysis Data Were Analyzed Using Statisticalmentioning
confidence: 99%
See 1 more Smart Citation